Main Memory Database Instant Recovery - Magalhães, Arlino; Monteiro, José Maria; Brayner, Ângelo (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2023)
Main Memory Databases (MMDBs) technology handles the primary database in Random Access Memory (RAM) to provide high throughput and low latency. However, volatile memory makes MMDBs much more sensitive to system failures. The contents of the database are lost in these failures. As a result, systems may be unavailable for a long time until the database recovery process has been finished. Therefore, novel recovery techniques are needed to repair crashed MMDBs as quickly as possible. This thesis presents MM-DIRECT, a recovery technique that enables MMDBs to schedule transactions immediately after the system startup. The approach also implements a tuple-level consistent checkpoint to reduce the recovery time. To validate the proposed approach, experiments were performed in a prototype implemented on the Redis database. The results show that the proposed instant recovery technique effectively provides high transaction throughput rates even during the recovery process and normal database processing.